Exploring the Effects of Electronic Payment Systems on Operational Efficiency - Esther Aine (Uganda Christian University, 2024)
This study titled “Exploring the effects of electronic payment systems on operational efficiency” focuses on the consumers around Mbarara City in Uganda. Its specific objectives are to analyze the cost-effectiveness of utilizing electronic payment systems compared to traditional payment methods, to analyze the risk of fraud associated with electronic payments compared to cash and finally to analyze the potential economic impacts of transitioning from paper-based to electronic based payment systems. A mixed-methods approach was employed, with qualitative interviews and some quantitative data. The primary data sources were business owners around Mbarara City, along with retrospective data from archives, conducted as a cross-sectional study. The study involved 100 relevant business owners, with a sample size of 65 determined using simple random sampling and stratified sampling methods, and data was collected through questionnaires. Findings were presented using tables. The study found that the implementation of electronic payment systems has positively impacted customer satisfaction because of their convenience and flexibility offered. In examining the risk of fraud associated with electronic payment systems, we discovered that most people perceive electronic payments as having a higher risk of being compromised through methods like phishing attacks. However, gaps existed in response to such issues; like in the research it was discovered that despite the technological advancements and security measures put in place to secure electronic payments they are significantly still insecure. Overall, the use of electronic payment systems improved transaction process time and this indicated that most of the organizations/businesses perceive a positive impact leading to increased efficiency and productivity. In the research it was also discovered that many of the organizations are prepared for the future advancements in relation to electronic payment systems.